The Use of Think Talk Write Strategy in Improving Students’ Writing Spoof Ability on English Department FKIP USI Pematangsiantar - Anita Purba; Semaria Eva Elita Girsang (Budapest International Research and Critics University, 2020)
The aims of the research were: (1) To know that Think-Talk-Write Strategy can improve the students’ writing Spoof ability and (2) To describe the process of Think-Talk-Write-Strategy in improving students’ writing Spoof ability. This research was conducted at English Department FKIP USI at the fifth Semester in the Academic Year of 2018/2019. The population were 21 students. The qauntitative data were taken from the scores of the pre-test and post-test. The total score is 1111, the mean 52, 9 thus, in the post test found the total score is 1701, the mean 81.Think-Talk-Write Strategy inspired both the students and the researcher in improving the ability of English especially on writing. The students could practice their skill of English in the different situation and treatment. They could express their idea or opinion freely as the researcher only became mediator during the activities of Think-Talk-Write Strategy as it was student-centred. In fact, the students’ cooperation increased. They helped each other, communicated using English, and built the idea, imagination and opinion that they wanted to compose in their writing during applying Think-Talk-Write Strategy.